Daily oral cyanocobalamin supplementation in Beagles with hereditary cobalamin malabsorption (Imerslund‐Gräsbeck syndrome) maintains normal clinical and cellular cobalamin status - Kook, Peter H. (J Vet Intern Med, 2018)
BACKGROUND: Efficacy of PO cobalamin (Cbl) supplementation in dogs with hereditary Cbl malabsorption (Imerslund‐Gräsbeck syndrome, IGS) is unknown. OBJECTIVES: To evaluate PO Cbl supplementation in Beagles with IGS previously treated parenterally. We hypothesized that 1 mg cyano‐Cbl daily PO would maintain clinical and metabolic remission. ANIMALS: Three client‐owned Beagles with IGS and 48 healthy control dogs. METHODS: Prospective study. Daily PO cyanocobalamin (cyano‐Cbl; 1 mg) supplementation was monitored for 13 (2 dogs) and 8 months (1 dog). Health status was assessed by owner observations. Methylmalonic acid (MMA)‐to‐creatinine concentrations were measured using an ultra‐performance liquid chromatography‐tandem mass spectrometry (UPLC‐TMS) method on urine samples collected monthly. Concurrent measurements of serum MMA concentration (n = 7; UPLC‐TMS) were available for 1 dog. RESULTS: All dogs remained in excellent health during PO supplementation. Urine MMA remained consistently low in 2 dogs (median, 2.5 mmol/mol creatinine; range, 1.2‐9; healthy dogs [n = 30], median, 2.9 mmol/mol creatinine; range, 1.3‐76.5). Urine MMA ranged from 38.9‐84.9 mmol/mol creatinine during the first 6 months in 1 dog already known to excrete comparable amounts when supplemented parenterally. Brief antibiotic treatment for an unrelated condition after 6 months resulted in low urine MMA (median, 2.8 mmol/mol creatinine; range, 1.9‐4.8) for the next 7 months. All concurrent serum MMA concentrations (median, 651 nmol/L; range, 399‐919) before and after month 6 were within the established reference interval (393‐1476 nmol/L; n = 48). CONCLUSIONS AND CLINICAL IMPORTANCE: One milligram of cyano‐Cbl daily PO appears efficacious for maintaining normal clinical status and normal cellular markers of Cbl metabolism in Beagles with IGS.